Rainwater Harvesting Planning using Infiltration Wells in Amlapura City Karangasem Regency - Mawiti Infantri Yekti; Mecris Mides Yumame; Kadek Diana Harmayani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Amplapura is located in the highlands having a potential area of green open land which can absorb rainwater freely into the ground. However, in recent times, land conversion has begun to develop with new housing buildings, Griya Galiran Regency Housing. Furthermore, the effectiveness of the land area is still able to absorb water and maintain groundwater balance. A rainwater harvesting plan (RH) is needed, or, more popularly, rainwater harvesting. In this area. The aim is to provide a portion of residential land space for rainwater infiltration into the pores or soil cavities using the infiltration well method. The results showed that the Griya Galiran Regency Housing had an acceptable sand soil type and absorbed soil quickly, with a soil permeability coefficient (k) of 0.0014 cm/s. Designing the dimensions of the infiltration well at the Griya Galiran Regency Housing with an area of 70 m2 based on SNI 03-2453-2002 for a circular cross-section, an infiltration well with a diameter of 1.2 m with a depth of 2 m is made. In contrast, as a rectangular cross-section, an infiltration well has a side length of 1 m with a depth of 2 m.